2017
DOI: 10.1039/c7ra11122c
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial polyketides from Trichoderma koningiopsis QA-3, an endophytic fungus obtained from the medicinal plant Artemisia argyi

Abstract: Five new and two known antimicrobial polyketides were identified from endophytic Trichoderma koningiopsis QA-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Similar to Penicillium, Trichoderma species also produce many bioactive secondary metabolites, such as polyketides, terpenoids, alkaloid, butenolides, etc [20]. As such, some novel compounds were isolated from a few endophytic Trichoderma species associated with the host plants, and demonstrated a wide range of bioactivities including cytotoxic [21], anti-inflammatory [22], antibacterial [23], and antifungal activities [24,25]. Pu et al reported that a T. atroviride strain isolated from Camptotheca acuminate could independently produce camptothecin in the fermentation process, with yields of 197.8 μg/l [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Penicillium, Trichoderma species also produce many bioactive secondary metabolites, such as polyketides, terpenoids, alkaloid, butenolides, etc [20]. As such, some novel compounds were isolated from a few endophytic Trichoderma species associated with the host plants, and demonstrated a wide range of bioactivities including cytotoxic [21], anti-inflammatory [22], antibacterial [23], and antifungal activities [24,25]. Pu et al reported that a T. atroviride strain isolated from Camptotheca acuminate could independently produce camptothecin in the fermentation process, with yields of 197.8 μg/l [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the NOESY experiment, NOEs from H‐4 to H‐9 and H 3 ‐17 and from H‐8 α to H‐2 α and H‐9 indicated the cofacial orientation of these groups ( Figure 4), while correlation from H‐7 to H‐8 β placed these protons on the other side of the molecule. Based on the octant rule for the cyclohexenones, [22–24] the positive Cotton effect (CE) at 310 nm in the ECD spectrum of 2 ( Figure 5) determined the absolute configuration at C‐4 as ( S ), and the positive CEs around 256 and 224 nm assigned the absolute configuration as (7 R ,9 S ,10 S ). Therefore, compound 2 was an epimer at C‐4 of 7‐ O ‐methylkoninginin D and named as 4‐ epi ‐7‐ O ‐methylkoninginin D. Compound 2 could be clearly detected in the HPLC profile ( Figure S38 ) of the initial AcOEt extract of the fungus (without touching of MeOH during extraction procedures) and thus supporting that this compound is not an artifact.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is of paramount importance to accurately identify any mycotoxins that might be produced by a fungal species that is to be used as BCA to ensure they are not capable of producing (types/amounts or both) of harmful mycotoxins during the biocontrol process. Several polyketides have been shown to display antimicrobial activities against agro-pathogenic fungi (Shi et al., 2017). Polyketides have been linked to other roles in fungi, including virulence, abiotic stress resistance and conidia pigmentation (Beltrán-García et al., 2014; Yao et al., 2016).…”
Section: Resultsmentioning
confidence: 99%